Phonological Analysis of Language Development in Graphically Improved Students of SLB Darussalam - Hel Seftiani (Universitas Sebelas Maret, 2022)
The aim of this research is to analyze the influence of language development on Darussalam SLB students, especially those with intellectual disabilities. Mental retardation is a condition of a person whose intelligence is far below the average of normal people and is characterized by limited intelligence and incompetence in social interactions. This is a type of phonological disorder that affects a person's language development. Qualitative methods with data collection techniques through observation, interviews and language tests were used in this research. and involving Darussalam SLB students with mental retardation as samples for this research. The results of the research show that each child with disabilities has different speaking abilities, there are children who can read fluently and their articulation is clearly pronounced but there are several words that they cannot pronounce, there are children who can read fluently but their articulation is less clear because of a defect in their equipment. said the child, there are also those who can read fluently but the articulation is not clear and there are still several words that they cannot pronounce because of weaknesses in their speech organs. Phonological disorders can have a negative impact on children's language development, both in terms of phonology, semantics, syntax and pragmatics. Children with phonological disorders tend to have difficulty producing language sounds, understanding the meaning of words, constructing sentences, and using language appropriately in social contexts. These findings emphasize the importance of appropriate intervention and treatment to help children with phonological disorders develop optimal language skills.